Small Bowel Obstruction due to Migrated Intragastric Balloon: A Case Report and Literature Review - Min Yien Tan; Kar Yin Fok; Huong Nguyen; Senarath Edirimanne; Michael Devadas (Case Reports in Surgery)
Introduction. With the rising rate of obesity world-wide, there are increasing weight loss options including operative and non-operative techniques. Endoscopic intragastric balloons (IGB) have gained popularity since its inception three decades ago and is viewed as a less invasive alternative to bariatric surgery. However, complications, though rare and probably under-reported, can be associated with significant morbidity and mortality. Case Presentation. We present the case of a 44-year-old woman who presented with a two-day history of upper abdominal pain, nausea, and obstipation, on the background of a Spatz3™ Balloon (Spatz FGIA, Great Neck, NY, USA) endoscopically placed seven months prior. Computed tomography scan confirmed small bowel obstruction due to a migrated IGB, requiring laparotomy and enterotomy for retrieval. Conclusion. With the development of new types of IGB and increasing usage, it is important to monitor for issues and complications.